Lignicolous freshwater ascomycota from Thailand: Phylogenetic and morphological characterisation of two new freshwater fungi: Tingoldiago hydei sp. nov. And t. clavata sp. nov. And eastern Thailand - Li Xu (2020)
© 2020 Pensoft Publishers. All rights reserved. Lignicolous freshwater fungi represent one of the largest groups of Ascomycota. This taxonomically highly diverse group plays an important role in nutrient and carbon cycling, biological diversity and ecosystem functioning. The diversity of lignicolous freshwater fungi along a north-south latitudinal gradient is currently being studied in Asia. In this paper, we introduce two novel freshwater taxa viz. Tingoldiago hydei sp. nov. and T. clavata sp. nov. which were collected from freshwater substrates in Eastern Thailand. Morphological comparison based on the size of ascomata, asci and ascospores, as well as multi-gene phylogenetic analyses based on LSU, SSU, ITS and TEF1-α DNA sequences, supports their placement in Tingoldiago (Lentitheciaceae). Descriptions and illustrations of these two new species are provided.